Penyerapan Logam Kadmium Menggunakan Batubara Lignit yang Diekstraksi dan Tanpa Diekstraksi dengan Pelarut Organik - Destri Yunita (Seminar Nasional Lahan Suboptimal, 2021)
Yunita D. 2021. Metal cadmium absorption using extracted and unextracted lignite coal with organic solvents. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 482-489. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Lignite coal with a large surface area, having carboxylate and phenol functional groups can be used as cadmium metal adsorbent, but the impact of lignite coal extraction on the absorption of cadmium metal content using organic solvents needs to be investigated. This study aimed to find out the adsorption power of cadmium metal ions by lignite coal extracted using the best organic solvents and without extraction at optimum absorption conditions.The extraction method was soxhletation using n-hexane, chloroform, and ethanol as solvents. The measurement of cadmium metal content was determined by the Atomic Absorption Spectrometry (AAS) method, where the optimum conditions for the absorption of cadmium metal ions were determined by varying the stirring time (3, 8, 15, 30, 45, 60 minutes), pH (2, 3, 4, 5, 6, 7), and metal ion concentration of cadmium (1, 3, 5, 7, 9 ppm). The results of the study showed that the adsorption ability of lignite coal extracted with ethanol was higher than the other solvents used. The optimum conditions for absorption by the extracted adsorbent were reached at 60 minutes, pH 7, and a concentration of 9 ppm while the adsorbent without extraction was reached at 60 minutes, pH 5, and a concentration of 9 ppm. The absorption of cadmium metal ions produced by each adsorbent extracted and without extraction was 0.1668 mg/g and 0.1674 mg/g.Thus, the lignite coal without extraction is the most suitable as cadmium metal adsorbent. Further research is needed on the pore size of the extracted lignite coal and the functional groups present in the lignite coal in the adsorption process.